Barriers in care pathways and unmet mental health needs in LGBTIQ + communities. (19th May 2022) - Silveri, Giada; Schimmenti, Simone; Prina, Eleonora; Gios, Lorenzo; Mirandola, Massimo; Converti, Manlio; Fiorillo, Andrea; Pinna, Federica; Ventriglio, Antonio; Galeazzi, Gian Maria; Sherriff, Nigel; Zeeman, Laetitia; et al.
Abstract: Lesbian, gay, bisexual, transgender, intersex, queer people and minority gender identities and sexualities (LGBTIQ+) are often stigmatized and experience discrimination in health care settings, leading to poorer mental health outcomes and unmet needs compared to heterosexual and cisgendered peers. It is thus imperative that mental health providers consider and address structural challenges in order to reduce mental health inequalities of this population. This narrative review assessed the barriers that may prevent access to care and the pathways for care in LGBTIQ + communities. PubMed, PsycInfo, Embase, and Scopus were searched for papers published between December 2021 and February 2022. A total of 107 papers were included with studies reflecting five themes: (1) Unmet mental health needs; (2) Young people; (3) Substance abuse and addiction; (4) Barriers and pathways to care; and (5) Interventions. Findings demonstrate that LGBTIQ + people experience stigmatization and higher rates of substance misuse and mental ill health, which may lead to barriers in accessing health care services, and fewer tailored interventions being provided. These findings have implications for policy, health care screening, and how specialist services are structured. Substantial gaps in the evidence-base exist, and future research should examine how mental health care providers can challenge social issues that maintain discriminatory and stigmatizing practices, and support LGBTIQ + individuals to sustain their resilience.